Realisasi Penerimaan Pajak Ditinjau Dari Perspektif Pendapatan Negara - Syska Lady Sulistyowatie; Rizky Windar Amelia (Postgraduate Program Merdeka University, 2020)
Tax is the largest revenue of a country since it can be renewed flexibly in accordance with the developments. Tax is something that can be imposed on citizens as the reciprocity over the contra-actions made by the government, but of course the contra-achievement cannot be directly enjoyed by its citizens. The tax is levied by the government to finance the State budget. The population in this study is tax revenue consisting of Income tax (PPh), Value Added Tax Sales Tax on Luxury Goods (PPNPPnBM), Property Tax Land and Building Rights Acquisition Fees (PBBBPHTB), Other Taxes, Import Duties, Excise, and Export Taxes. While the sample in this study is Income Tax, Value Added Tax Sales Tax on Luxury Goods, Property Tax Land and Building Rights Acquisition Fees, Other Taxes, Import Duties, Excise, and Export Taxes from 2015-2019. The results of the study of Value Added Tax Sales Tax on Luxury Goods and Import Duties variables have a positive and significant effect on state income, while the variables Income tax, property tax land and building rights acquisition fees, Other Taxes, Excise, and Export Taxes have no effect on state revenues. DOI: https://doi.org/10.26905/afr.v3i1.4602